2012
DOI: 10.1007/s11606-012-2072-y
|View full text |Cite
|
Sign up to set email alerts
|

The Average Lifespan of Patients Discharged from Hospital with Heart Failure

Abstract: The development of risk-adjusted life-tables for heart failure populations is feasible and mirrored those with advanced malignant diseases. Average life span varied widely across clinical risk strata, and may be less accurate among those at or near their end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Furthermore, it is important to note that our cohort of AMI patients was assembled from 2004 to 2005, and treatment patterns may have changed over time. Finally, although the calculation of projected life expectancy was previously validated, [9][10][11][12] we were unable to validate our estimates against the actual estimates in the EFFECT cohort because the majority of patients were still alive in our study cohort.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, it is important to note that our cohort of AMI patients was assembled from 2004 to 2005, and treatment patterns may have changed over time. Finally, although the calculation of projected life expectancy was previously validated, [9][10][11][12] we were unable to validate our estimates against the actual estimates in the EFFECT cohort because the majority of patients were still alive in our study cohort.…”
Section: Discussionmentioning
confidence: 91%
“…Prior study has suggested that the lower treatment propensity for higher risk patients is associated with clinicians' concerns of patients experiencing adverse events with acute reperfusion therapy. 11,19 To overcome this care gap, we think a paradigm shift in improving our understanding of life expectancies is needed. The primary issue is that the majority of current clinical prediction tools estimate baseline risks of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Multimorbidity greatly increases the risk of hospitalization and death among HF patients. 4,5,6,7 Efforts to reduce these risks are particularly challenging given the limited data available to guide clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients who survive from myocardial infarction (MI) are often left with a significant impairment of left ventricular systolic function due to ischemic cardiomyopathy triggering the remodeling of the left ventricle and fibrosis. Ischemic cardiomyopathy can lead to a poor quality of life and a poor prognosis with high mortality of more than 25% within the first year of diagnosis [2,3]. Current treatment strategies, including optimal pharmacotherapy, cardiac resynchronization therapy, and implantable cardioverter-defibrillators, slow progression of the MI to heart failure, improve systolic function, and prevent fatal arrhythmias that can cause sudden cardiac death [4][5][6][7]; however, they cannot stimulate cell regeneration to recover the loss of functional myocytes.…”
Section: Introductionmentioning
confidence: 99%